Pengaruh Korean Wave dan Gaya Hidup Hedonis terhadap Keputusan Pembelian Album Official BTS (Studi pada ARMY Indonesia) - Hanny Fahirra; Anik Lestari Andjarwati (Jurnal Ilmu Manajemen, 2022)
The Covid-19 pandemic has caused the entertainment industry to suffer from delays in activities, including concerts and album releases. One of the entertainment industries that can survive is the K-Pop industry. Entertainment agencies in South Korea are experiencing intense competition in releasing new albums due to concert delays. The album sales in 2020 increased by 64% compared to the previous year. This K-Pop trend makes fans seek pleasure by spending their money buying albums from idol groups they admire. The research aims to analyze the effect of the Korean Wave and hedonic lifestyle on purchase decisions for BTS official albums on ARMY Indonesia. This study uses a sample of 200 respondents, namely ARMY Indonesia, who had purchased BTS official albums with an age range of 16 to 35 years. The sampling method is judgmental sampling with a Likert scale as a measuring instrument. The analysis in this study uses multiple linear regression equation models. The result showed that Korean Wave and hedonic lifestyle variables positively and significantly affected purchasing decisions. This research is expected to be used by Big Hit Entertainment to redesign their companies' marketing strategies by paying attention to the Korean Wave and hedonistic lifestyle.